2014
DOI: 10.1051/0004-6361/201322925
|View full text |Cite
|
Sign up to set email alerts
|

Observations and analysis of phase scintillation of spacecraft signal on the interplanetary plasma

Abstract: Aims. The phase scintillation of the European Space Agency's Venus Express (VEX) spacecraft telemetry signal was observed at X-band (λ = 3.6 cm) with a number of radio telescopes of the European Very Long Baseline Interferometry (VLBI) Network in the period 2009-2013. Methods. We found a phase fluctuation spectrum along the Venus orbit with a nearly constant spectral index of −2.42 ± 0.25 over the full range of solar elongation angles from 0 • to 45 • , which is consistent with Kolmogorov turbulence. Radio ast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…These observations were carried out under different weather conditions: the first day under heavy clouds, the second with strong wind and rain, and the last with clear sky. As described in Molera Calvés et al (), the atmospheric conditions have little influence on the results. The results indicated that the worst measurement in terms of detection accuracy of the spacecraft signal was achieved with clear sky, on 6 April 2015.…”
Section: Methods and Observationsmentioning
confidence: 62%
See 3 more Smart Citations
“…These observations were carried out under different weather conditions: the first day under heavy clouds, the second with strong wind and rain, and the last with clear sky. As described in Molera Calvés et al (), the atmospheric conditions have little influence on the results. The results indicated that the worst measurement in terms of detection accuracy of the spacecraft signal was achieved with clear sky, on 6 April 2015.…”
Section: Methods and Observationsmentioning
confidence: 62%
“…The analysis of spacecraft radio signals allows one to determine the variation of the phase of a radio signal that is related to the variations in the electron density ( δ n e ) (see more in section 2.2). In Molera Calvés et al (), we presented a study based on observations of Venus Express with VLBI radio telescopes. In that paper we established, as stated in previous studies (Coles et al, ; Woo et al, , ), that the phase scintillation index ( σ Sc ) is approximately proportional to the interplanetary plasma TEC TECσSc, where σ Sc is a measure of the level of fluctuations in the phase of the spacecraft signal caused by the propagation in a turbulent media.…”
Section: Methods and Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is achieved by performing precise Doppler tracking of the spacecraft carrier signal and near-field VLBI observations in phase-referencing mode (Duev et al 2012(Duev et al , 2016Bocanegra-Bahamón et al 2018). PRIDE is suitable for various applications in planetary and space science, such as determination of planetary ephemerides (Dirkx et al 2017), characterization of the interplanetary plasma (Molera et al 2014) and detection of interplanetary coronal mass ejection (ICME) (Molera et al 2017). In this work we present another application: the characterization of planetary atmospheres and/or ionospheres by means of radio occultation observations.…”
Section: Introductionmentioning
confidence: 99%